Optimizing Early Childhood Learning Interest through a Differentiated Learning Approach - Johana Kastanja; Hamid Patilima (Journal of Childhood Development, 2024)
Every student definitely has various characteristics and learning interests that are different from each other. This is a challenge for teachers in carrying out teaching and learning activities. Teachers should be able to accommodate the diversity, needs and learning interests of students because this is the key to success in achieving learning goals. However, in reality, many children have low interest in learning because learning is not focused on children and learning needs are not in accordance with their characteristics. This research aims to optimize children's interest in learning through the application of differentiated learning. This research uses a classroom action research (PTK) approach which is carried out in 2 cycles. Each cycle consists of planning, implementation and observation and reflection stages. The location of the research was at the Kebayoran Lama State Kindergarten 01, South Jakarta, with research subjects of group B students totaling 16 students. The data collection techniques used in this research are interviews and observation. The research results showed that there was an increase from pre-cycle, to cycle I and then cycle II. The percentage of interest in learning in the pre-cycle was 49.91%. In cycle I it was 81.40%, and in cycle II it reached 96.79%. Thus it can be said that children's interest in learning can be optimized through a differentiated learning approach because differentiated learning is a learning approach that is designed to meet their needs, interests and child's talent.